A Theoretical Framework for the Creative Process of Theatrical Costume Design for Historically Set Productions. (January 2019) - Jablon-Roberts, Sara; Sanders, Eulanda
Millions of Americans see theatrical productions every year, each with performers clothed via costume design. The purpose of this study was to systematically examine the creative process of costume design for historically set theatrical productions. Sixteen Broadway costume designers were interviewed. Data analysis revealed that though each designer and every production is different, these costume designers approached historically set productions similarly. They believed that the presentation of history is essential, but they have their own inclination toward historical accuracy. Guided by their inclinations, they designed costumes by considering three independent production factors (applicability, attainability, and performability) and implementing four iterative strategies (incubation, research, role-playing, and historical manipulation). Through these findings, the authors developed a theoretical framework for the creative process of costume design for historically set productions. Semiotics and symbolic interactionism were applied. Analysis showed that both were unconsciously embraced by the contemporary Broadway costume designers who participated in this study.